Antibacterial, antioxidant and tyrosinase-inhibition activities of pomegranate fruit peel methanolic extract - Fawole Olaniyi A; Makunga Nokwanda P; Opara Umezuruike (BMC, 2012)
Abstract Background This study evaluated, using in vitro assays, the antibacterial, antioxidant, and tyrosinase-inhibition activities of methanolic extracts from peels of seven commercially grown pomegranate cultivars. Methods Antibacterial activity was tested on Gram-positive (Bacillus subtilis and Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli and Klebsiella pneumonia) using a microdilution method. Several potential antioxidant activities, including radical-scavenging ability (RSA), ferrous ion chelating (FIC) and ferric ion reducing antioxidant power (FRAP), were evaluated. Tyrosinase enzyme inhibition was investigated against monophenolase (tyrosine) and diphenolase (DOPA), with arbutin and kojic acid as positive controls. Furthermore, phenolic contents including total flavonoid content (TFC), gallotannin content (GTC) and total anthocyanin content (TAC) were determined using colourimetric methods. HPLC-ESI/MSn analysis of phenolic composition of methanolic extracts was also performed. Results Methanolic peel extracts showed strong broad-spectrum activity against Gram-positive and Gram-negative bacteria, with the minimum inhibitory concentrations (MIC) ranging from 0.2 to 0.78 mg/ml. At the highest concentration tested (1000 μg/ml), radical scavenging activities were significantly higher in Arakta (83.54%), Ganesh (83.56%), and Ruby (83.34%) cultivars (P< 0.05). Dose dependent FIC and FRAP activities were exhibited by all the peel extracts. All extracts also exhibited high inhibition (>50%) against monophenolase and diphenolase activities at the highest screening concentration. The most active peel extract was the Bhagwa cultivar against monophenolase and the Arakta cultivar against diphenolase with IC50 values of 3.66 μg/ml and 15.88 μg/ml, respectively. High amounts of phenolic compounds were found in peel extracts with the highest and lowest total phenolic contents of 295.5 (Ganesh) and 179.3 mg/g dry extract (Molla de Elche), respectively. Catechin, epicatechin, ellagic acid and gallic acid were found in all cultivars, of which ellagic acid was the most abundant comprising of more than 50% of total phenolic compounds detected in each cultivar. Conclusions The present study showed that the tested pomegranate peels exhibited strong antibacterial, antioxidant and tyrosinase-inhibition activities. These results suggest that pomegranate fruit peel could be exploited as a potential source of natural antimicrobial and antioxidant agents as well as tyrosinase inhibitors.